Real‐world persistence with liraglutide 3.0 mg for weight management and the SaxendaCare® patient support program - Wharton, Sean (Obes Sci Pract, 2020)
OBJECTIVE: Weight management medications can significantly increase patients' chances of achieving a clinically meaningful weight loss if patients persist with treatment. This retrospective observational study of de‐identified medical records of 311 patients is the first real‐world study examining persistence with liraglutide 3.0 mg in Canada, and also investigates associations between the SaxendaCare® patient support program and persistence and weight loss. METHODS: Overall persistence was assessed, as well as associations of enrollment in SaxendaCare®, persistence and weight loss. RESULTS: Overall mean (standard deviation) persistence with liraglutide 3.0 mg was 6.3 (4.1) months, and 67.5% (n = 210) and 53.7% (n = 167) of patients persisted for ≥4 and ≥ 6 months, respectively. Enrollment in SaxendaCare® was associated with significantly longer persistence with liraglutide 3.0 mg and greater weight loss. Patients enrolled in SaxendaCare® (n = 119) persisted for 7.9 (4.0) versus 5.2 (3.8) months for those not enrolled (n = 184) (p < 0.001), and had significantly greater percent weight loss after 6 months regardless of the duration of their persistence (−7.9% vs −5.5% from baseline, p < 0.01). CONCLUSIONS: These findings suggest that, in clinical settings, persistence with liraglutide 3.0 mg can exceed 6 months, and that enrolling in SaxendaCare® may be associated with comparatively longer persistence and, regardless of persistence, greater weight loss.